Criminal Legal Protection for Cases of Carrying Away Livestock in Livestock Agreements - Lestari, Arum Ayu; Lestariningsih (Journal of Development Research, 2025)
Livestock Gaduh is an activity that has been carried out for generations, where the Gaduh giver entrusts his livestock to be cared for by the Gaduh recipient with a profit-sharing agreement. The absence of an agreement between the 2 (two) parties by only relying on trust has caused various conflicts, one of which is the crime of embezzlement or fraud. The purpose of this study is to make Gaduh givers more careful in entrusting their livestock to be entrusted to someone (the Gaduh recipient). The method in this writing uses normative juridical with a statutory and conceptual approach. The results of this study are that many people only rely on customary law to place trust in the Gaduh giver so that when the Gaduh recipient has bad intentions to sell his livestock without the knowledge of the Gaduh giver, it cannot be processed administratively, because there is no written evidence. Therefore, criminal law as an ultimum remidium is one solution to resolve this problem